Crosslinguistic influence at the syntax proper: Interrogative subject–verb inversion in heritage Spanish - Cuza, Alejandro (The international journal of bilingualism : cross-disciplinary, cross-linguistic studies of language behavior, 2013)
This study examines the potential effects of crosslinguistic influence in the acquisition of subject–verb inversion in Spanish matrix and embedded wh-questions among Spanish heritage language learners living in the United States. The results from an acceptability judgment task and a written production task administered to 17 US-born heritage speakers indicate crosslinguistic influence effects. The effects are more evident with embedded interrogatives than with matrix questions. A follow-up study with the heritage speakers also shows less inversion behavior with embedded questions in oral production but higher performance levels than in written production. The findings are discussed in relation to interface vulnerability approaches and current debates on the selective nature of crosslinguistic influence in L2 and bilingual development.